2020
DOI: 10.1088/1755-1315/503/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Daylighting Analysis: A Contribution to the Urban Planning of the City of Marilândia - ES (Brazil)

Abstract: Daylighting is one of the environmental resources that deliver quality to the built area by making it more comfortable and efficient and by promoting people’s well-being, besides reducing the consumption of electrical energy. The amount of daylighting indoors is related to the construction features, whose parameters are those of the urban legislation, as well as to the location features where the building stands. This research aimed to get a better knowledge of the interference of the urban typologies of Maril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, it is a major factor in the potential of building envelopes (especially roofs) to collect solar radiation for photovoltaic electricity production [22]. Drago et al [23] state that "The amount of daylighting indoors is related to the construction features, whose parameters are those of the urban legislation, as well as to the location features where the building stands". Determining daylight/sunlight levels hitting building envelope in an urban context, especially in high-density ones, can also have an economic impact on the building value, or, within the same building, to specific units located on different floors: Turan et al [24] carried out a study in Manhattan which showed that in a dense urban environment with a gradient in daylight levels, tenants greatly value high amounts of daylight, with a higher willingness to pay compared to spaces with a lower amount of daylight.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a major factor in the potential of building envelopes (especially roofs) to collect solar radiation for photovoltaic electricity production [22]. Drago et al [23] state that "The amount of daylighting indoors is related to the construction features, whose parameters are those of the urban legislation, as well as to the location features where the building stands". Determining daylight/sunlight levels hitting building envelope in an urban context, especially in high-density ones, can also have an economic impact on the building value, or, within the same building, to specific units located on different floors: Turan et al [24] carried out a study in Manhattan which showed that in a dense urban environment with a gradient in daylight levels, tenants greatly value high amounts of daylight, with a higher willingness to pay compared to spaces with a lower amount of daylight.…”
Section: Introductionmentioning
confidence: 99%